PENGENDALIAN KUALITAS PROSES PRODUKSI OBAT TABLET DENGAN MENGGUNAKAN METODE SIX SIGMA DI PT MDF - ENDAH PRATIWI; HARI MOEKTIWIBOWO; INDRAMAWAN INDRAMAWAN (JURNAL TEKNIK INDUSTRI, 2021)
PT MDF is a company that moving in pharmaceutical manufacturing industry which have tablet and capsule as product. The number of defects medicinal tablets product when tabletting process become one of problems that exist in the company. Identifying the root cause of the problem is carried out in order to control the quality of medicinal tablets product. The method that used to control the quality is with implementation of Six Sigma to improve the quality of medicinal tablets product produced by the company. Quality improvement of medicinal tablets product is carried out by implementing Six Sigma method with DMAIC. In phase D (Define) is carried out by specify the types of defects and determination of CTQ. Phase M (Measure), measurements were taken in the form of UCL, CL, LCL, DPMO and Sigma Levels. The DPMO value in August to November 2018 is 1.800 DPMO with sigma level 4,41. Phase A (Analyze), the determination of the dominant type of defect was carried out with pareto diagrams and cause-effect analysis using fishbone. Based on the Pareto diagram, the dominant type of defects is Broken Tablet. Hereafter, cause and effect diagram (fishbone) is carried out with five main factors causing defects of Broken Tablet including Man (Lack of training, not careful), Machine (Lack of maintenance), Material (Low quality of raw materials), Method (Lack of procedures application), Environment (Work area is thermal). Phase I (Improve) is carried out with corrective actions from the results of the analysis using 5W+1H method. Last, phase C (Control) with control over the improvements that have been made.Keywords : DMAIC, Six Sigma, Quality Control, Fishbone, Medicinal Tablets, DPMO